Biology and Management of Praxelis (Praxelis clematidea) in Ornamental Crop Production - Yuvraj Khamare; Chris Marble; Shawn Steed; Nathan Boyd (EDIS)
Praxelis is a newly emerging weed species in Florida, one that Plant Protection and Quarantine (PPQ) is considering adding to the federal noxious weed list. The plant can be easily misidentified and confused with Ageratum houstonianum (bluemink) and Conoclinium coelestinum (blue mistflower) as well as several other species that have similar flower characteristics. This new 5-page article is written for green industry professionals and others to aid in the identification and management of praxelis in and around ornamental plants. Written by Yuvraj Khamare, Chris Marble, Shawn Steed, and Nathan Boyd, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep585